2017
DOI: 10.1021/acs.langmuir.7b02692
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ionic Strength on the Deposition of Metal–Phenolic Networks

Abstract: Metal-phenolic networks (MPNs) are a versatile class of self-assembled materials that are able to form functional thin films on various substrates with potential applications in areas including drug delivery and catalysis. Different metal ions (e.g., Fe, Cu) and phenols (e.g., tannic acid, gallic acid) have been investigated for MPN film assembly; however, a mechanistic understanding of the thermodynamics governing MPN formation remains largely unexplored. To date, MPNs have been deposited at low ionic strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 32 publications
4
66
0
1
Order By: Relevance
“…Similar results were observed for the Co-TA2 dimer systems, with an average of 6 ± 2 water oxygens positioned within a 4 Å radius of cobalt. The Co-TA2 dimers had a larger contact area (20 ± 1%) when compared to the Fe-TA3 dimers (13 ± 3%, as determined by our previous study; 46 Table S4). Additionally, the Co-TA2 dimers had relatively more aromatic contacts and fewer intermolecular hydrogen bond occupancies when compared to the Fe-TA3 dimers (13 ± 5 and 3 ± 1% compared to 9 ± 3 and 9 ± 2%, respectively; Table S4).…”
Section: Resultssupporting
confidence: 75%
“…Similar results were observed for the Co-TA2 dimer systems, with an average of 6 ± 2 water oxygens positioned within a 4 Å radius of cobalt. The Co-TA2 dimers had a larger contact area (20 ± 1%) when compared to the Fe-TA3 dimers (13 ± 3%, as determined by our previous study; 46 Table S4). Additionally, the Co-TA2 dimers had relatively more aromatic contacts and fewer intermolecular hydrogen bond occupancies when compared to the Fe-TA3 dimers (13 ± 5 and 3 ± 1% compared to 9 ± 3 and 9 ± 2%, respectively; Table S4).…”
Section: Resultssupporting
confidence: 75%
“…The effect of ionic strength on the spray formation of TA-Fe III films was also examined, where an increase in ionic strength led to thicker and rougher MPN coatings ( Figure S16), which is consistent with our previous study on the formation of TA-Fe III films by discrete deposition. 40 On the basis of the above observations, it can be concluded that the physicochemical properties (thickness and complex coordination state) of the MPN coatings prepared via spray assembly can be tuned by adjusting the pH, solvent, ionic strength, and/or precursor molar ratio and concentration. 41 spray coating allows for the rapid patterning of large areas.…”
Section: Preparation Of Spray-assembled Mpns With Different Metals Anmentioning
confidence: 96%
“…Moreover, the MPN coating is substrate independent, i.e., it can be formed on almost any type of surfaces due to the nonspecific binding of polyphenols with various surfaces and the simultaneous cross-linking of polyphenols by metal ions. In addition, the MPN-coating morphology, roughness, thickness, degradation profiles, and surface functionalities can be engineered through choice of the building blocks (51,60,61). Owing to their excellent biocompatibility, MPN coatings have also been exploited at the interface of bioentities such as proteins, alkaloids, polysaccharides, and even living cells and tissues under physiological conditions (62).…”
Section: Organic-inorganic Hybrid Materialsmentioning
confidence: 99%